El derecho a la intimidad y su relación con el alcance de la facultad notarial para materializar documentos desde página web o de cualquier soporte electrónico. - Castillo Gonzaga, Alexander Michael (2024)
This research examines the relationship between the right to privacy and the notary's authority to formalize electronic documents or web pages, particularly those originating from social networking platforms and other digital media. The Notarial Code, as per Resolution 083- 2020, permits the materialization of electronic documents, a process in which a notary converts a digital file into a physical document, thereby granting its legal validity. However, this practice raises significant concerns regarding the right to privacy, as protected by the Ecuadorian Constitution, and international entities such as the International Covenant on Civil and Political Rights and the American Convention on Human Rights. These legal frameworks guarantee protection against arbitrary or abusive interference in individuals' private lives and correspondence. The objectives of this research were to analyze the implications of notarial materialization of private conversations obtained from social networks. Evaluate whether this procedure aligns with constitutional and international standards, and assess its compliance with established judicial processes. The applied methodology and resulting analysis reveal irregularities in certain notarial acts. This may infringe upon individuals' privacy by materializing intimate conversations without the consent of the involved parties. The conclusions indicate that the materialization of documents from web pages or any electronic source conflicts with fundamental privacy rights. Recommendations are proposed to adapt these practices to ensure stronger protection of privacy rights in the context of digital information.